2009
DOI: 10.1002/elan.200804449
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite Films Obtained by Electrochemical Codeposition of Conducting Polymers and Carbon Nanotubes

Abstract: The electrochemical growth of carbon nanotubes (CNTs) -conducting polymer composites offers the ability to produce three-dimensional nanostructured films that combine the redox pseudo-capacitive charge storage mechanism of conducting polymers with the high surface area and conductivity of CNTs [1 -3]. In this paper we report the electropolymerization and characterization of polypyrrole films (PPy) doped with poly (m-aminobenzenesulfonic acid) (PABS) functionalized single-walled carbon nanotubes (SWCNTs) (PPy/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 17 publications
3
30
0
Order By: Relevance
“…The voltammetric signal of the nitrophenyl group in 0.1 M TBATFB in ACN can be observed at a rather low cathodic potential (approximately À1.5 V), nitrobenzene being reversibly reduced by one electron to its stable radical anion. [16,17] On repetitive scans, this reversible wave gradually decreases because of the protonation of the radical anion of the p-nitrophenyl group by residual water. In the case of grafting at SWCNTs electrodes, the reversibility could not be evidenced at these cathodic potentials when transferring to a pure electrolyte solution.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The voltammetric signal of the nitrophenyl group in 0.1 M TBATFB in ACN can be observed at a rather low cathodic potential (approximately À1.5 V), nitrobenzene being reversibly reduced by one electron to its stable radical anion. [16,17] On repetitive scans, this reversible wave gradually decreases because of the protonation of the radical anion of the p-nitrophenyl group by residual water. In the case of grafting at SWCNTs electrodes, the reversibility could not be evidenced at these cathodic potentials when transferring to a pure electrolyte solution.…”
Section: Resultsmentioning
confidence: 98%
“…[16,17] The selected molecules used for SWCNTs functionalisation were chosen both for the opposite electronic effects of the aryl substituents and their electroactivity after grafting. We observed that electrochemistry can be an advantageous technique for qualitative analysis of grafting on SWCNTs, the functionalisation of SWCNTs with electroactive groups (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These composite materials have distinct, complementary properties of the individual components with a synergistic effect [45]. Combination of CPs and CNTs produces a new composite material with improved electrochemical and mechanical properties that were not observed in the individual components [46].…”
Section: Introductionmentioning
confidence: 99%
“…One is the electropolymerization of a polymer film on electrode surfaces already modified by the adsorbed CNT coatings [31][32][33]47]. The other is to dissolve the monomer in a suspension of CNTs, and then co-deposit the polymer with the CNTs into a composite coating on the electrode surface [45,48,49].…”
Section: Introductionmentioning
confidence: 99%